2016
DOI: 10.1126/science.aai8611
|View full text |Cite
|
Sign up to set email alerts
|

A general, modular method for the catalytic asymmetric synthesis of alkylboronate esters

Abstract: Due to the critical role of stereochemistry in determining properties such as biological activity, as well as growing interest in sustainability, there is a strong impetus to develop catalytic and enantioselective methods for synthesis. Alkylboranes are an important family of target compounds, serving as useful intermediates, as well as endpoints (medicines such as Velcade™), in fields such as pharmaceutical science and organic chemistry. Because C–B bonds can be transformed into a wide variety of C–X bonds (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
108
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(109 citation statements)
references
References 36 publications
0
108
0
1
Order By: Relevance
“…[7,8] If the intermediate radical might instead react with the Ni complex furnishing D,t hen catalyst-based stereocontrol might be realized even though the process involves radical intermediates.T he underlying principles that would enable such ap rocess are aligned with other metal-catalyzed intermolecular dicarbofunctionalizations [9] of alkenes,w hich take place either through carbometalation/cross-coupling [10] pathways or through radical addition/cross-coupling cascades. [8] Lastly,i nr egards to as tarting point for reaction conditions,w ec onsidered that asystem developed by Fu [13] and co-workers for the enantioconvergent cross-coupling of organozinc reagents to ahaloboronic esters would be appropriate as this process appears to involve selective recombination of aN ic omplex with an a-boryl radical similar to the transformation of C to D described above. [12] To begin our investigation of the transition-metal/radical process proposed in Scheme 1c,w ef irst sought as toichiometric organometallic reagent that would react with Ni-based intermediates,b ut would not react directly with threecoordinate vinylboron reagents.W hile organolithium, and to some extent Grignard reagents,w ill convert vinylB(pin) into the derived "ate" complex, it was found that neither aryl nor alkyl zinc reagents would react with vinylB(pin).…”
mentioning
confidence: 99%
“…[7,8] If the intermediate radical might instead react with the Ni complex furnishing D,t hen catalyst-based stereocontrol might be realized even though the process involves radical intermediates.T he underlying principles that would enable such ap rocess are aligned with other metal-catalyzed intermolecular dicarbofunctionalizations [9] of alkenes,w hich take place either through carbometalation/cross-coupling [10] pathways or through radical addition/cross-coupling cascades. [8] Lastly,i nr egards to as tarting point for reaction conditions,w ec onsidered that asystem developed by Fu [13] and co-workers for the enantioconvergent cross-coupling of organozinc reagents to ahaloboronic esters would be appropriate as this process appears to involve selective recombination of aN ic omplex with an a-boryl radical similar to the transformation of C to D described above. [12] To begin our investigation of the transition-metal/radical process proposed in Scheme 1c,w ef irst sought as toichiometric organometallic reagent that would react with Ni-based intermediates,b ut would not react directly with threecoordinate vinylboron reagents.W hile organolithium, and to some extent Grignard reagents,w ill convert vinylB(pin) into the derived "ate" complex, it was found that neither aryl nor alkyl zinc reagents would react with vinylB(pin).…”
mentioning
confidence: 99%
“…The Fu group defined a Ni-catalyzed cross-coupling of racemic alkyl bromides with a variety of electrophiles. [18] In these transformations a secondary radical likely combines with an alkyl metal species to provide a dialkyl metal species 6 . Reductive elimination generates the optically active cross-coupled product ( 7 ).…”
mentioning
confidence: 99%
“…[43][44][45] a-Haloboronic esters have been used in tin-mediated (Scheme 1A) [46][47][48][49] and metal-catalyzed radical processes. Finally,1 -borylated alkyl radicals were involved in the elegant nickel-catalyzed alkylation and arylation of a-haloboronic esters developed by the Fu [54] and Martin [55] groups,respectively.1-Borylated alkyl radicals have also been generated from Barton esters [56] and xanthates [45] as well as through radical addition to vinylboronates. [53] Interestingly,p inacol iodomethylboronic Figure 1.…”
mentioning
confidence: 99%